CFRP contribution to load-carrying capacity of retrofitted geopolymer concrete beams. (February 2023) - Ozturk, Mehdi; Sengun, Kadir; Arslan, Guray
Abstract: In this study, reference geopolymer concrete (GC) beams were loaded up to the failure state with a three-point bending test to obtain load–deflection behavior. These damaged reference GC beams were then repaired, strengthened with Carbon Fiber Reinforced Polymer (CFRP) in both shear and flexure. These retrofitted GC beams have been then tested in the same conditions as reference GC beams and the effect of the CFRP strengthening on the strength and behavior was investigated. The load-carrying capacities of the retrofitted GC beams were higher than the reference GC beams in all series. The increase in capacities due to CFRP strengthening was higher in retrofitted GC beams without stirrups than in retrofitted beams with stirrups. The initial stiffness of the retrofitted GC beams were lower than those of the reference GC beams. This decrease was more evident in GC beams without stirrups than in GC beams with stirrups. Strengthening with CFRP enhanced the deflection and ductility capacities of the repaired GC reference beams without stirrups compared to the reference GC beams. The experimental CFRP contribution to shear strength was tried to be estimated using the equations proposed for the CFRP contribution in reinforced concrete (RC) beams. The predicted contribution of CFRP to shear strength using all investigated equations was greater than the experimentally obtained CFRP contribution.